Molecular characterization of accessions of crabgrass (Digitaria nuda) and response to ametryn - Vieira, Viviane Cristina [UNESP]; Alves, Pedro Luís da Costa Aguiar [UNESP]; Picchi, Simone Cristina [UNESP]; Lemos, Manoel Victor Franco [UNESP]; Sena, Janete Apparecida Desidério [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2010)
Digitaria species are sugar cane crop weeds in Brazil and are being controlled with herbicides, although there are some reports of control failure, notably to the triazine group. Molecular techniques are recommended to analyze the genetic variability in weeds. RAPD (Random Amplified Polymorphic DNA), PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment Length Polymorphism) and, in combination with sequencing, allow the localization of resistance genes, as well as possible mutations related to the onset of resistant individuals in some species. Thus, the objective of this work was to characterize ten accessions of Digitaria spp. by RAPD and PCR-RFLP markers, to sequence a conserved region of the psbA gene and evaluate the accessions response to ametryn. As showed by molecular analysis there was high genetic similarity among the accessions, all of them presented similar genetics profiles and were susceptible to ametryn.

As espécies de Digitaria são plantas daninhas nas lavouras de cana-de-açúcar no Brasil e estão sendo controladas com herbicidas, porém há alguns relatos de falha no controle, notavelmente ao grupo das triazinas. Técnicas moleculares são recomendadas para análise da variabilidade genética em plantas daninhas, como o RAPD (DNA Polimórfico Amplificado ao Acaso) e PCR-RFLP (Reação da Polimerase em Cadeia - Polimorfismo no Comprimento de Fragmentos de Restrição) e, aliadas ao sequenciamento, permitem a localização de genes de resistência, bem como possíveis mutações relacionadas ao surgimento de indivíduos resistentes em algumas espécies. Com isso, o objetivo deste trabalho foi caracterizar dez acessos de Digitaria spp. por meio de marcadores RAPD e PCR-RFLP, sequenciar uma região conservada do gene psbA e analisar a resposta destes à ametrina. Pela análise molecular houve elevada similaridade genética entre os acessos, pois todos apresentaram perfis genéticos semelhantes e foram suscetíveis à ametrina.
Caracterização molecular de acessos de capim-colchão (Digitaria nuda) e resposta à ametrina
Keywords: Digitaria; psbA gene; RAPD; Sequencing; Triazine; Weed; Digitaria; Gene psbA; RAPD; Sequenciamento; triazina; Planta daninha